Macrophage Transcriptomic Alterations Driven by Alphavirus-Based Cancer Immunotherapy Vectors - Ksenija Korotkaja; Darija Lapina; Zhanna Rudevica; Anna Zajakina (Journal of Immunology Research)
Cancer cells promote the polarisation of tumour-associated macrophages (TAMs) into pro-tumorigenic M2-like phenotype, contributing to cancer progression. Reprogramming TAMs by viral immunotherapy vectors represents a promising strategy for cancer therapy. However, the factors driving macrophage reprogramming into a tumour-suppressing M1-like phenotype in response to viral vectors remain unclear. Alphaviral vectors, such as Semliki Forest virus (SFV), indirectly influence macrophages through cancer cell infection, cytokine gene delivery and tumour microenvironment (TME) modulation. This study examines macrophage transcriptomic alterations induced by SFV vectors. Murine mammary cancer cells were infected with SFV delivering tumour necrosis factor-α (TNFα) or interferon-γ (IFNγ) genes. Conditioned media from infected cells were used to treat bone marrow-derived macrophages (BMDMs) with subsequent analysis of the transcriptome. As a result, SFV-infected cancer cells significantly altered cytokine and chemokine profiles, reducing immunosuppressive factors (e.g., IL-10) and increasing inflammatory mediators (e.g., CXCL10 and CCL4). RNA sequencing revealed upregulation of genes associated with antigen presentation, interferon responses and M1 polarisation in macrophages treated with SFV/TNFα and SFV/IFNγ-conditioned media. SFV/IFNγ inhibited cancer-associated pathways (angiogenesis, glycolysis and extracellular matrix (ECM) remodelling) and enhanced cytotoxic lymphocyte (CTL) chemoattractants (CXCL9 and CXCL10). SFV/TNFα selectively upregulated Mmp2, Mmp14 and Ccl22. All SFV vectors upregulated PD-L1 (Cd274) expression. The study demonstrates that alphavirus-mediated gene delivery to cancer cells can impact macrophages, inducing proinflammatory responses and reprogramming them into anti-cancer phenotype. However, combining SFV/IFNγ with immune checkpoint inhibitors could potentially improve therapeutic efficacy by mitigating virus-induced suppressive signals in the TME.